Unilateral multiple lichen striatus treated with tacrolimus ointment: a case report - Vukićević, Jelica (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2009)
A previously healthy 11-year-old boy with multiple, unilateral lichen striatus(LS) on the left side of the body is described. The distribution of the lesions corresponded to the lines of Blaschko. Histology of the lesional skin was compatible with LS. Two years after the onset of the linear eruption,treatment with tacrolimus ointment resulted in significant improvement over a short period of time. To our knowledge, this is the first time that the use of tacrolimus for successful treatment of LS with multiple lesions has been reported.
Keywords: Child; Drug Therapy; Immunosuppressive Agents; Imunosupresivi; Lichenoid Eruptions; Lihenoidni izpuščaji; Mazila; Ointments; Otrok; Pathology; Tacrolimus; Takrolimus; Therapeutic Use